Premature mortality due to cervical cancer: study of interrupted time series - Maria Isabel do Nascimento; Felipe Corrêa Massahud; Nathália Giácomo Barbosa; Cássio Destefani Lopes; Vanessa da Costa Rodrigues (Universidade de São Paulo, 2020)
ABSTRACT OBJECTIVE: To verify the effect of the Pact for Health on premature mortality (30-69 years) attributed to cervical cancer in Brazil and its macroregions, using interrupted time series analysis. METHODS: Segmented regression was used to assess "change in level" and "change in trend" in premature mortality rates attributed to cervical cancer considering the post-Pact period (2010-2018), controlling by the pre-Pact period (1998-2006). Understanding the triennium 2007-2009 as essential for the adoption and implementation of the policy, it was excluded from the main modeling, but assessed in the sensitivity analysis. RESULTS: From 1998 to 2018, there were more than 119,000 deaths due to cervical cancer in women aged 30 to 69 years in Brazil. The Northern region experienced the highest rates (> 20 per 100,000). Comparing with baseline (1998-2006), segmented regression showed a progressive increase in changing trend from cervical cancer deaths in Brazil as a whole (coefficient = 0.513; 95%CI 0.430 to 0.596) and in the Southeast region (coefficient = 0.515; 95%CI 0.358 to 0.674), South region (coefficient = 0.925; 95%CI 0.642 to 1.208), and Midwest region (coefficient = 0.590; 95%CI 0.103 to 1.077). The Northeast region presented the most promising effects with immediate reduction in change level (-0.635; 95%CI −1.177 to −0.092) and progressive reduction in the changing trend of premature deaths (coefficient= −0.151; 95%CI −0.231 to −0.007). CONCLUSIONS: Premature mortality rates due to cervical cancer are high in Brazil and its macroregions. This interrupted time series was not able to reveal the effectiveness of initiatives related to the Pact for Health on premature deaths from cervical cancer nationally and in all macroregions equally. The best results are restricted to the Northeast region.